2013
DOI: 10.1113/jphysiol.2012.245233
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous properties of central lateral and parafascicular thalamic synapses in the striatum

Abstract: To understand the principles of operation of the striatum it is critical to elucidate the properties of the main excitatory inputs from cortex and thalamus, as well as their ability to activate the main neurons of the striatum, the medium spiny neurons (MSNs). As the thalamostriatal projection is heterogeneous, we set out to isolate and study the thalamic afferent inputs to MSNs using small localized injections of adeno-associated virus carrying fusion genes for channelrhodopsin-2 and YFP, in either the rostra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 81 publications
(110 reference statements)
12
100
1
Order By: Relevance
“…Finally, this LTD was blocked by NMDAR antagonist (R-CPP 10 μM) (Figure 5K, 95 ± 7 % of baseline, n = 5; p =0.44, Wilcoxon), indicating that LTD induced by oSTDP paradigm at thalamostriatal synapses is NMDAR-dependent rather than eCB-dependent. This finding, together with a recent report (Ellender et al, 2013), suggest that thalamostriatal synapses express a different form of LTD that does not involve CB1R activation.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Finally, this LTD was blocked by NMDAR antagonist (R-CPP 10 μM) (Figure 5K, 95 ± 7 % of baseline, n = 5; p =0.44, Wilcoxon), indicating that LTD induced by oSTDP paradigm at thalamostriatal synapses is NMDAR-dependent rather than eCB-dependent. This finding, together with a recent report (Ellender et al, 2013), suggest that thalamostriatal synapses express a different form of LTD that does not involve CB1R activation.…”
Section: Resultssupporting
confidence: 78%
“…It is interesting that the oSTDP protocol could induce an NMDAR-dependent LTD that is insensitive to eCB. It has been shown that thalamostriatal inputs from Pf exhibit NMDAR-dependent LTD, regardless of using ‘pre-post’ or ‘post-pre’ STDP induction protocols (Ellender et al, 2013). This could imply that when salient stimuli emerge with background stimulation, attentional shift mediated by thalamostriatal system wanes.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that reduced thalamostriatal synaptic input is specific to dMSNs in parkinsonian animals. Although our study did not selectively target Pf, other work has found distinct synaptic properties at Pf vs. central lateral thalamic inputs (Ellender et al, 2013), indicating that it will be critical to learn whether changes to thalamostriatal inputs in parkinsonian animals apply only to specific intralaminar nuclei or more broadly.…”
Section: Discussionmentioning
confidence: 87%
“…These mechanisms may be absent at axoshaft PF synapses. Perhaps to compensate for this anatomical feature, PF synapses have a robust complement of NMDAR-type glutamate receptors [78]. The significance of these unique properties of PF synapses is unclear but could be related to the poly-sensory, alerting nature of the information relayed by PF [79].…”
Section: Introductionmentioning
confidence: 99%